From Basics of Coordination Chemistry to Understanding Cisplatin-analogue Pt Drugs - Akitsu, Takashiro; Tsvetkova, Dobrina; Yamamoto, Yuma; Nakane, Daisuke; Kostova, Irena (Current Pharmaceutical Design, 2023)
Background: Cisplatin, a platinum complex discovered by Rosenberg in 1969, has long been known as the first metal-based anticancer agent. Since then, various similar derivatives of cisplatin have been investigated for pharmacological activity, and the approved complexes have been applied as drugs. Objectives: The aims of the current study are: 1) to summarize the advantages and dose-limiting effects of the approved and unapproved chemotherapy platinum cytostatics, 2) to develop new strategies for the development of platinum anticancer drugs, and 3) to clarify the important factors for the mechanism of action of platinum complexes. Methods: A search was conducted in the literature databases, and the obtained information was summarized and analyzed. Results: Myelosuppression is the main dose-limiting effect and the reason for the disapproval of platinum complexes, such as picoplatin, enloplatin, miboplatin, sebriplatin, zeniplatin, spiroplatin, iproplatin, and ormaplatin. From the basic point of view of inorganic coordination chemistry, such as theoretical calculations, crystal structures of model complexes, docking structures with nucleic acid molecules, spectroscopy, and biological aspects, the importance of physicochemical properties of inorganic platinum complexes for their mechanism of action has been indicated. Spectroscopic methods, such as FTIR, NMR, X-ray crystal structure analysis, and fluorescence microscopy, are important for the investigation of the conformational changes in the binding of platinum complexes and DNA. Conclusion: In the development of platinum complexes, strong anti-cancer drug activity, low toxicity, and resistance can be obtained by the application of polynuclear platinum agents, complexes with targeted activity, and nanoparticle formulations. Electronic structure, stereochemical, and thermodynamic properties are essential for understanding the reaction mechanism of platinum complexes.
Keywords: Cisplatin